2021
DOI: 10.3390/nu13093271
|View full text |Cite
|
Sign up to set email alerts
|

Ghee Butter from Bovine Colostrum Reduces Inflammation in the Mouse Model of Acute Pancreatitis with Potential Involvement of Free Fatty Acid Receptors

Abstract: Acute pancreatitis (AP) is an inflammatory disease that causes severe tissue damage. Ghee butter from bovine colostrum (GBBC) is a clarified butter produced by heating milk fat to 40 °C and separating the precipitating protein. As colostrum mainly contains fatty acids (FAs), immunoglobulins, maternal immune cells, and cytokines, we hypothesized that it may exert anti-inflammatory effects. We investigated the effects of GBBC on experimental AP in mice. Two intraperitoneal (ip) injections of L-arginine (8%) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The only negative annotation found in the review of ghee was its association with neonatal tetanus as a result of its application on the umbilical cord wound [ 111 ]. Studies have shown that ghee exhibits anti-inflammatory effects in acute pancreatitis, reducing inflammation in pancreatic and lung tissues [ 112 ]. Additionally, ghee promotes cell proliferation and enhances migration of keratinocytes, indicating its positive influence on wound healing processes [ 113 ].…”
Section: Review Of Modern Literature On Ghee In Context Of the 15 Ben...mentioning
confidence: 99%
“…The only negative annotation found in the review of ghee was its association with neonatal tetanus as a result of its application on the umbilical cord wound [ 111 ]. Studies have shown that ghee exhibits anti-inflammatory effects in acute pancreatitis, reducing inflammation in pancreatic and lung tissues [ 112 ]. Additionally, ghee promotes cell proliferation and enhances migration of keratinocytes, indicating its positive influence on wound healing processes [ 113 ].…”
Section: Review Of Modern Literature On Ghee In Context Of the 15 Ben...mentioning
confidence: 99%